LOS ANGELES, CALIFORNIA - PRUETT B (Tufts Archival Research Center, 2007)
Memo from Bob Pruett to George Minshew regarding establishing a relationship between the tobacco industry and organizations in Los Angeles, CA. Suggests that relationships be formed with various restaurant associations. Projects on 1992 funding.